Lipid accumulation impairs natural killer cell cytotoxicity and tumor control in the postoperative period - Niavarani, Seyedeh R; Lawson, Christine; Bakos, Orneala; Boudaud, Marie; Batenchuk, Cory; Rouleau, Samuel; Tai, Lee-Hwa (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Natural killer (NK) cell dysfunction following cancer surgery has been shown to promote metastases. Recent studies demonstrate an emerging role for lipids in the modulation of NK cell innate responses. However, the mechanisms involved in lipid modulation of NK cell postoperative anti-tumor function are unknown. This current study will determine whether the lipid accumulation via scavenger receptors on NK cells is responsible for the increase in postoperative metastasis. Methods Lipid content in mouse and human NK cells was evaluated by flow cytometry. NK cell scavenger receptor (SR) expression was measured by microarray analysis, validated by qRT-PCR and flow cytometry. NK cell ex vivo and in vivo tumor killing was measured by chromium-release and adoptive transfer assays, respectively. The mediating role of surgery-expanded granulocytic myeloid derived suppressor cells (gMDSC) in SR induction on NK cells was evaluated using co-culture assays. Results NK cells in surgery-treated mice demonstrated increased lipid accumulation, which occurred via up-regulation of MSR1, CD36 and CD68. NK cells with high lipid content had diminished ability to lyse tumor targets ex vivo. Adoptive transfer of lipid-laden NK cells into NK cell-deficient mice were unable to protect against a lung tumor challenge. Granulocytic MDSC from surgery-treated mice increased SR expression on NK cells. Colorectal cancer surgical patients showed increased NK cell lipid content, higher CD36 expression, decreased granzyme B and perforin production in addition to reduced cytotoxicity in the postoperative period. Conclusions Postoperative lipid accumulation promotes the formation of metastases by impairing NK cell function in both preclinical surgical models and human surgical colorectal cancer patient samples. Understanding and targeting the mechanisms underlying lipid accumulation in innate immune NK cells can improve prognosis in cancer surgical patients.